Empowering Elementary Students: A Model for Enhancing Literacy and Numeracy Skills to Overcome Learning Loss - Mufarrihul Hazin; Nur Wedia Devi Rahmamawati; Muhammad Turhan Yani; Suyatno Ladiqi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Quality education is essential for national progress, but low literacy and numeracy competencies among students negatively affect Indonesia's educational outcomes. This study aimed to identify learning losses in literacy and numeracy among elementary school students, provide targeted interventions and mentoring, and evaluate their impact. A qualitative field study was conducted in 10 elementary schools in Hulu Sungai Selatan Regency, South Kalimantan. The study involved 20 students per school, spanning grades 2 to 6. Data were collected through 10-question assessments for each student, interviews with principals, teachers, and parents, as well as observation and documentation. The findings revealed significant learning losses during the pandemic, with a 56.5% decline in numeracy competence and a 62.95% decline in literacy competence. Targeted interventions included inquiry learning, quantum teaching, project-based learning, and contextual learning models. Post-intervention, literacy competence increased by 31.2%, while numeracy competence improved by 17.5%. The results demonstrate that tailored learning models and strategies effectively address learning losses. Teachers play a critical role in adapting these approaches to match students' cognitive development and targeted competencies. Enhancing literacy and numeracy requires innovative teaching models and continuous adaptation of strategies to students’ needs. These findings emphasize the importance of flexible and student-centered learning practices to mitigate learning losses and improve educational outcomes.